The bark of holm oak (Quercus ilex, L.) for airborne Cr(VI) monitoring. (January 2015) - Minganti, Vincenzo; Drava, Giuliana; De Pellegrini, Rodolfo; Anselmo, Marco; Modenesi, Paolo; Malaspina, Paola; Giordani, Paolo
Highlights: The bark of holm oak is used as a bioindicator of hexavalent chromium. Extraction/AAS determination is an excellent estimation of Cr(VI) concentration. Samples collected from industrially polluted, urban, and rural areas were analysed. Urban samples show significantly higher concentrations compared to rural samples. Abstract: In this work, the bark of holm oak was used as a bioindicator to study the atmospheric distribution of Cr(VI). The chosen method (alkaline extraction and atomic absorption determination) was found in the literature, adapted for use with the matrix involved, and validated. The method had some limits, but provided an excellent estimation of Cr(VI) concentrations with good sensitivity and a reasonable time of analysis and cost. Thirty-four samples of holm oak collected in three areas characterised by different possible sources of pollution (the area near a former chromate production plant, an urban area, and a rural "reference" area) were analysed, obtaining concentrations ranging from 1.54 to 502 μg g −1 near the industrial plant, ranging from 0.22 to 1.35 μg g −1 in the urban area, and mostly below the detection limit (0.04 μg g −1 ) in the rural area. The bark of holm oak proved to be a good bioindicator to detect Cr(VI) in the environment. The extraction procedure followed by atomic absorption analysis is simple, provides good sensitivity, and it is suitable for environmental studies.